Most common sequelae of trauma in primary teeth to permanent successor teeth: an integrative literature review (Research, Society and Development, 2022)
Dental trauma is a public health problem, common in preschool and school age groups, with possible immediate and late consequences for the permanent dentition, both at the time of trauma and due to the resulting consequences. The aim of the study is to evaluate the most common complications of trauma in deciduous teeth for the permanent dentition. Searches in electronic data were conducted using PUBMED and LILACS with the following keywords or descriptors in health sciences (DeCS): dental trauma, deciduous tooth, permanent tooth and sequelae and the respective Medical Subject Headings (MesH): tooth injuries, tooth deciduous, dentition permanent. Studies published without year of publication restriction and without language restriction until August 2022 were searched. The search strategy retrieved 61 potentially relevant records. The first screening resulted in 19 studies that remained for full text reading. Finally, six studies were included for descriptive synthesis. It is concluded that there may be an association between age and the type of trauma with the possible consequences for permanent teeth. The younger the child, the greater the possibility of causing immediate or late sequelae in the permanent tooth, with enamel defects (opacities and hypoplasias) being the most common alterations.